THE WATER DECADE 1981–1990 - Guest, Iain (SCHOOL SCIENCE, 2013)
Ask someone from an affluent city suburb to characterise water and you would probably get a curious stare and something along the lines of “colourless, tasteless and abundant.” But ask the same question to a villager in the Third World, and the answer might well provide a web of insights into a life of extraordinary hardship. For here water does not come from the ubiquitous tap. It has to be carried—usually by women—from a well or a river up to a mile away, several times a day. It is usually insufficient, and what there is may be so badly contaminated that it risks causing severe diarrhoea. The fact that safe drinking water and its corollary, proper sanitation, are taken for granted in the more affluent countries but are a matter of life and death in the developing world has been monitored with increasing concern by WHO in recent years. This concern expressed itself in the UN agencies’ own way of generating a sense of political urgency—the large international conference.